IS THERE ANTI-JUDAISM IN THIS TEXT?: SOME REFLECTIONS ON MATT 23 - Dragutinović, Predrag (Sacra scripta, 2019)
I read Matt 23 as a text describing a ‘family conflict’. The speaker of the words in Matt 23 is Jesus, who is a Jew. The text was written by Matthew, a Jew, and the addressees of the text are Jews. This text focuses on Jewish religious authorities and those who suffered under the restrictions and formalities imposed by such leaders. There is no ethnic element in this text. It is not concerned with how one ethnic group−Jews−relates to another ethnic group—gentiles. The polemic is not about differences between two ethnic groups, but about religious behavior within a single ethnic group—Jews. The victims of religious formalism are Jews, not pagans. Every reading of Matt 23 that finds anti-Judaism in the text should be considered inadequate. Such readings fail to grasp the true meaning of the text. This text should be read and understood as a criticism of religious formalism. As such, it has relevance in every time and place, whenever and wherever religion fosters violence and becomes repressive to ordinary people. This text can be helpful in prompting self-criticism, which I consider important for every religious system.